Country Partnership Framework for the Democratic Republic of Ethiopia for the Period FY18-FY22 - World Bank Group (World Bank, Washington, DC, 2017)
Ethiopia has achieved substantial progress in economic, social and human development over the past decade. The country partnership framework (CPF) draws on the findings of the World Bank Group (WBG's) 2016 systematic country diagnostic (SCD) for Ethiopia. Following a decade of strong economic growth in Ethiopia, the CPF addresses the challenges of forging a growth path that is more broadly inclusive and sustainable. This CPF adopts a spatial lens through which this five-year program will seek to deliver bold results and to tackle two of the greatest spatial challenges to Ethiopia’s quest to achieve lower middle-income status by 2025.